2013
DOI: 10.4236/ijoc.2013.33027
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Carvenone by Montmorillonite-Catalyzed Isomerization of 1,2-Limonene Oxide

Abstract: Montmorillonite was considered as a good heterogeneous catalyst for the isomerization of 1,2-limonene oxide into carvenone under solvent-free condition. Both conventional heating and green activations were tested in this research. The microwave-assisted isomerization afforded carvenone in high yield within only 6 minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…This compound can be also used in syntheses of very valuable compounds for the organic and polymers industry. For example: Nguyen et al described a method of carvone obtaining by the isomerization of 1,2-epoxylimonene 8 and Byrne et al showed the method of the synthesis of a special polymer (poly(limonene) carbonate) from 1,2-epoxylimonene and CO 2 -this polymer has properties similar to polystyrene 9 . The applications of 1,2-epoxylimonene in medicine are also very important: a decreasing of the oxidative stress and curing of the anxiety states 10 .…”
Section: Introductionmentioning
confidence: 99%
“…This compound can be also used in syntheses of very valuable compounds for the organic and polymers industry. For example: Nguyen et al described a method of carvone obtaining by the isomerization of 1,2-epoxylimonene 8 and Byrne et al showed the method of the synthesis of a special polymer (poly(limonene) carbonate) from 1,2-epoxylimonene and CO 2 -this polymer has properties similar to polystyrene 9 . The applications of 1,2-epoxylimonene in medicine are also very important: a decreasing of the oxidative stress and curing of the anxiety states 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding epoxide products, namely 1,2-epoxy-p-menth-8-ene (LimEp) and 1,2:8,9-diepoxy-p-menthane (LimDiEp), have wide application potential. LimEp has been employed in metal coatings, varnishes, and printing inks [79], and in the synthesis of fragrances [95,96], pharmaceuticals [97] and food additives, biodegradable polycarbonates (by copolymerization with CO2) [98], and polyesters (by copolymerization with cyclic anhydrides) [99]. LimDiEp is used as a solvent and in epoxy resins as a reactive diluent, MeOle and MeLin can be obtained by the transesterification of vegetable oils such as olive, palm, rapeseed, corn, sesame, soybean, and sunflower [78][79][80].…”
Section: Epoxidation Of Biomass-derived Olefinsmentioning
confidence: 99%